PSYCHOLOGY OF STUDENT DEVELOPMENT WITH A GUIDANCE COUNSELING APPROACH - Januar Saputra; Annisa Apriliyanti; Siti Mayang Sari; Syukri Azwar Lubis (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research uses a descriptive qualitative method whose data sources are obtained through interviews and describing several real documentation related to the phenomena written about. Sourced from several participants who became news sources obtaining problems regarding the psychology of student development. In relation to psychology, there is no meaningful use of counseling guidance in schools. The teacher's role in this problem is to provide motivation and clinical guidance for student development in everyday life. With polite, orderly, motivated and moral behavior, students must have proper guidance and direction from teachers, parents and support from the internal and external environment. The research obtained results that based on several sources, both personal and concrete interpersonal abilities, it is clear that the effort to see the psychology of student development significantly with current problems is through an effective counseling guidance approach so that counseling guidance teachers can contribute more to increasing change within themselves. student. The relationship between students and teachers has a continuous relationship between educators and educated people so that they get compassionate behavior and special attention to students.